Impacts of Climate Change on the Environment, Economy, and Society of China - Ding, Yongjian (Climate and Environmental Change in China: 1951–2012, 2015)
This chapter evaluates the characteristics and extent of impacts of modern climate change on the hydrology, ecology, agriculture, health, economy, and society of China. The impacts of climate change on water resources, hydrological processes, the cryosphere, and ocean hydrological processes are analyzed, as well as the impacts on land ecosystems, desertification, and soil erosion. The impact of global sea-level change on marine ecology and the coastal environment is comprehensively assessed. The chapter also summarized the impact of climate change on farming, animal husbandry, forestry, aquaculture, and fisheries.